PENINGKATAN PROFESIONALISME GURU DAN KUALITAS PEMBELAJARAN BIOLOGI DI SEKOLAH MELALUI LESSON STUDY - Sriyati, Mrs Siti (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2007)
This research was done to investigate impact of lesson study in order to improveteachers professionalism and the quality of teaching learning process in Biology.Although lesson study has been conducted since the year of 2005 at numerousschools- in Bandung, information on how far such activity does give impact toteacher as instructoi and teacher as observer has not been covered. The researchwas undertaken by spreading questions to the instructor as well as the observer.Furt5ermore, quaiity-of teaching learning process in the school was observed atSMP Lab. School and SMA Lab. School UPI. The research resulted in insight thatthrough lesson study, teachers both served as instructor and observer can improvesuch competency as pedagogy, professional, personality, social as clearlyinclicated in ., UU Guru dan Dosen l,1o. 14 Tahun 2005